Natal origin and age-specific egress of Pacific bluefin tuna from coastal nurseries revealed with geochemical markers - Rooker, Jay R.; Wells, R. J. David; Block, Barbara A.; Liu, Hui; Baumann, Hannes; Chiang, Wei-Chuan; Sluis, Michelle Zapp; Miller, Nathaniel R.; Mohan, John A.; Ohshimo, Seiji; Tanaka, Yosuke; Dance, Michael A.; et al. (Scientific reports, 2021)
Geochemical chronologies were constructed from otoliths of adult Pacific bluefin tuna (PBT) to investigate the timing of age-specific egress of juveniles from coastal nurseries in the East China Sea or Sea of Japan to offshore waters of the Pacific Ocean. Element:Ca chronologies were developed for otolith Li, Mg, Mn, Zn, Sr, and Ba, and our assessment focused on the section of the otolith corresponding to the age-0 to age-1 + interval. Next, we applied a common time-series approach to geochemical profiles to identify divergences presumably linked to inshore-offshore migrations. Conspicuous geochemical shifts were detected during the juvenile interval for Mg:Ca, Mn:Ca, and Sr:Ca that were indicative of coastal-offshore transitions or egress generally occurring for individuals approximately 4–6 mo. old, with later departures (6 mo. or older) linked to overwintering being more limited. Changepoints in otolith Ba:Ca profiles were most common in the early age-1 period (ca. 12–16 mo.) and appear associated with entry into upwelling areas such as the California Current Large Marine Ecosystem following trans-Pacific migrations. Natal origin of PBT was also predicted using the early life portion of geochemical profile in relation to a baseline sample comprised of age-0 PBT from the two primary spawning areas in the East China Sea and Sea of Japan. Mixed-stock analysis indicated that the majority (66%) of adult PBT in our sample originated from the East China Sea, but individuals of Sea of Japan origin were also detected in the Ryukyu Archipelago.